Ultrasound Biomicroscopic Diagnosis of Angle-closure Mechanisms in Vietnamese Subjects With Unilateral Angle-closure Glaucoma. Issue 2 (February 2018) - Do, Tan; Nguyen Xuan, Hiep; Dao Lam, Huong; Tran Tien, Dat; Nguyen Thi Thuy, Giang; Nguyen Do Ngoc, Hien; Verma, Sushma; Aung, Tin
Abstract : Objective: To identify the mechanisms of angle closure in the fellow eyes of Vietnamese subjects with unilateral primary angle-closure glaucoma (PACG) using ultrasound biomicroscopy (UBM) before and after prophylactic laser peripheral iridotomy (LPI). Design: This is a prospective observational study. Participants: Patients diagnosed with PACG in one eye and primary angle-closure suspect (PACS) in the other eye were included in this study, conducted from January 2014 to October 2014 at Vietnam National Institute of Ophthalmology. Materials and Methods: A total of 112 PACS fellow eyes of 112 patients presenting with unilateral PACG were evaluated. All subjects underwent standard ophthalmic clinical examination and UBM imaging a week before and after LPI. On the basis of UBM images, the angle-closure mechanism was defined according to the classification of Svend Vedel Kessing and John Thygesen as pupillary block (PB), plateau iris (PI), and mixed pattern. Results: The proportion of PACS subjects who showed PB was 86.6%, while 13.4% showed a PI configuration before LPI. After LPI the pre-LPI PB group was reclassified, with 55.4% showing pure PB, and 31.3% showing mixed mechanisms (PB and PI). The proportion of patients with PI remained unchanged (13.4%) even after LPI. After the LPI, the angle opening significantly increased in the PB subgroup (14.01±2.43 degrees, P <0.01) and reclassified mixed group (6.34±1.71 degrees, P <0.01) but remained almost unchanged in the PI group (1.81±0.98 degrees, P >0.05). Conclusion: On the basis of the UBM criteria, PI was found in 13.4% of PACS fellow eyes of Vietnamese subjects with PACG. The clinical and UBM features of patients showing PI before LPI remained almost unchanged after the procedure. The proportion of patients showing PB pre-LPI reduced from 86.6% to 55.4% showing the important role of mixed mechanisms in PACG.